Perancangan Sistem Informasi Manajemen Ruangan pada Dinas Pendidikan Kota Salatiga - Velda Prasetiyo; Hanna Prillysca Chernovita (KITA Institute, 2023)
In the era of information technology development as it is now needed a platform such as a website or application to facilitate the process and also activities on an activity or job. One of the activities in question is the existence of room management, when there is a loan of space to carry out meetings or socialization. In the process of borrowing this room there are still a lot of agencies that still use the system manually so that the level of efficiency is still low and less meet. In designing this system, the authors conducted a case study at the Department of Education Salatiga as a place of borrowing meeting rooms and socialization. If the agency has a website that is made to facilitate the process related to borrowing space, then later the agency is no longer needed to come to the Department of Education Salatiga. For that the author tries to design a system in order to facilitate the agencies in the process of borrowing space. And the selection of the web application platform is chosen to make it easier for agencies to use this service without having to install applications that will usually take up memory on the device and can be accessed anywhere by the user, in this web design researchers use Code Igniter software with PHP programming language.. In this study the method used the method used to analyze the problems in this study using the method of PIECES (Performance, Information, Economic, Control, Efficiency, Service). This information system is built to improve the management process of borrowing space more effectively and efficiently.